2010
DOI: 10.1073/pnas.1001253107
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 attenuates atherosclerotic lesions by targeting vascular cells

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a newly discovered homolog of ACE whose actions oppose those of angiotensin II (AngII). However, the underlying mechanisms by which ACE2 effectively suppresses early atherosclerotic lesions remain poorly understood. Here, we show, both in vitro and in vivo, that ACE2 inhibited the development of early atherosclerotic lesions by suppressing the growth of vascular smooth muscle cells (VSMCs) and improving endothelial function. In a relatively large cohort animal study (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 34 publications
3
109
0
Order By: Relevance
“…3,[84][85][86][87][88][89] CONCLUSIONS In summary, Ang-(1-7) is generated in the vascular wall and other tissues from Ang II by ACE2, resulting in a decrease in Ang II levels and an increase in Ang-(1-7) concentrations in the vessels. Thus, the ACE2-Ang-(1-7)-Mas axis counterregulates the classic RAAS in tissues responsible for blood pressure regulation and cardiovascular homeostasis.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 99%
See 1 more Smart Citation
“…3,[84][85][86][87][88][89] CONCLUSIONS In summary, Ang-(1-7) is generated in the vascular wall and other tissues from Ang II by ACE2, resulting in a decrease in Ang II levels and an increase in Ang-(1-7) concentrations in the vessels. Thus, the ACE2-Ang-(1-7)-Mas axis counterregulates the classic RAAS in tissues responsible for blood pressure regulation and cardiovascular homeostasis.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 99%
“…Concurrently, it was recently shown that genetic deletion of ACE2 significantly increases 83 plaque formation in atherosclerotic animals, which is decreased by targeted vascular ACE2 overexpression. 80,84 Consequently, these actions of the ACE2-Ang-(1-7)-Mas axis may be exploited in the treatment of atherosclerosis and other vascular diseases.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 99%
“…The immunohistochemical staining was performed as previously described 27. Sections were incubated with the primary antibodies against α‐SMA (1:200; Abcam, ab5694), monocyte/macrophage antigen [MOMA‐2] (1:200; MCA519G; AbD, UK), MMP2 (1:250; NovusBio, NB200‐193) and MMP9 (1:100; Abcam, ab38898).…”
Section: Methodsmentioning
confidence: 99%
“…Our study showed that ACE2 overexpression attenuated the progression of lesions and stabilized atherosclerotic plaques in rabbits, which were formed by endothelial injury and an atherogenic diet. 14 Sahara et al reported that ACE2 gene knock-out in mouse increased the severity of atherosclerosis and produced an inflammatory response in plaque, suggesting that ACE2 is an important role in anti-atherosclerosis. 15 Thatcher et al found that ACE2 deficiency increased atherosclerotic area and inflammatory response through regulation of the ratio of Ang II/Ang-(1-7) peptides.…”
Section: Discussionmentioning
confidence: 99%